The 'when' and 'where' of semantic coding in the anterior temporal lobe: Temporal representational similarity analysis of electrocorticogram data. (June 2016) - Chen, Y.; Shimotake, A.; Matsumoto, R.; Kunieda, T.; Kikuchi, T.; Miyamoto, S.; Fukuyama, H.; Takahashi, R.; Ikeda, A.; Lambon Ralph, M.A.
Abstract: Electrocorticograms (ECoG) provide a unique opportunity to monitor neural activity directly at the cortical surface. Ten patients with subdural electrodes covering ventral and lateral anterior temporal regions (ATL) performed a picture naming task. Temporal representational similarity analysis (RSA) was used, for the first time, to compare spatio-temporal neural patterns from the ATL surface with pre-defined theoretical models. The results indicate that the neural activity in the ventral subregion of the ATL codes semantic representations from 250 msec after picture onset. The observed activation similarity was not related to the visual similarity of the pictures or the phonological similarity of their names. In keeping with convergent evidence for the importance of the ATL in semantic processing, these results provide the first direct evidence of semantic coding from the surface of the ventral ATL and its time-course.